Impacts of feed dilution and lower solids retention time on performance of thermal hydrolysis/anaerobic digestion. (12th February 2019) - Higgins, Matthew J.; Beightol, Steven; DeBarbidillo, Christine; De Clippeleir, Haydee; Pathak, Bipin; Al‐Omari, Ahmed; Murthy, Sudhir N.
Abstract: The goal of this study was to evaluate using feed dilution/solids retention time (SRT) control to manage potential ammonia inhibition in highly loaded anaerobic digesters after thermal hydrolysis. The study compared three digesters operated at the same target volatile solids (VS) loading rate of 5.5 kg VS/d‐m 3, but at different feed concentrations resulting in SRTs of 10, 15, and 18 days. Lowering the feed concentration decreased the digester total ammonia nitrogen concentrations which averaged 1, 580, 2, 610, and 3, 080 mg NH 4 + ‐N/L for the 10‐, 15‐, and 18‐day digesters. The VS reduction and methane yields were equivalent for the 15‐ and 18‐day digesters and about 4% lower for the 10‐day digester. Ammonia inhibition of the 18‐day digester occurred early in the study, but the system acclimated over time. Feed dilution reduced the viscosity and the potential for volume expansion due to gas holdup and foaming. Practioner points: Feed dilution reduces digester ammonia concentrations and inhibition potential without sacrificing digester performance at lower SRTs. Feed dilution greatly reduces digester viscosity and associated issues with digester volume expansion due to gas holdup and foaming. Operating at the lower SRT does not impact cake solids after dewatering and substantially decreases polymer demand for conditioning.